FAKTOR-FAKTOR YANG MEMPENGARUHI PENDAPATAN ASLI DAERAH PROVINSI SUMATERA BARAT - Putri, Adek; Akbar, Urmatul Uska (Media Riset Ekonomi Pembangunan (MedREP), 2025)
This study aims to analyze the factors that influence the original regional income of West Sumatra province. This study uses a qualitative approach with secondary data from the 2017-2022 BPS (Central Statistics Agency) Survey. The results of the study indicate that the number of residents, the number of tourists and the accumulation of hotels and restaurants have a positive and significant effect on the original regional income in West Sumatra. While the economic growth variable does not affect the original regional income in West Sumatra.